Garden of fools - Hutchison, Robert (New Delhi Palimosest, 2012)
The looming spectre of death in the Ganga-Yamuna Doab made Proby Cautley wonder about the dichotomy of famin being a land of abundance. An artillery officer by training, the unlikely civil engineer in the East India Company's service - channelling the pristine snow-melt waters from the Himalayas into the parched fields through a network of unforgiving shadows of famine. It was a gritty struggle - fighting a recalcitrant colonial bureaucracy for approval and petty rivalry of other technocrats within John Company' hierarchy and disarming local superstitions.
Keywords: Fiction